Nonintensive topical gentamicin treatment of patients with severe epidermolysis bullosa caused by nonsense mutations - Ø. Sandanger; M. K. Torp; A. Glesaaen; H. R. Nilsen; J. C. Sitek (Wiley, 2024)
Abstract Background Severe epidermolysis bullosa (EB) is caused by premature termination codons (PTCs) in a significant minority of the patients. Topical gentamicin has been shown to increase wound healing and can restore protein translation in patients with EB through PTC suppression. However, only intensive treatment of limited wound areas have been reported previously. Objectives The objectives of this study is to investigate whether nonintensive topical gentamicin therapy is an effective wound‐healing treatment in patients with severe EB caused by PTCs. Methods A randomized, open‐controlled, single‐centre, single‐arm clinical trial designed to determine effectiveness at an individual level was performed. Each patient served as their own control and received topical 0.1% gentamicin ointment once daily for 6 weeks on all wounds on one body half. Wound areas were measured at Weeks 0 and 6. Change in wound areas at Week 6 compared with baseline was calculated and the changes in treated areas were compared with control areas. Immunohistochemistry was performed at Weeks 0 and 6. Results Four patients were included. One patient withdrew before completion. No significant effect on wound healing was seen. Immunohistochemistry analysis supported successful PTC suppression in two patients. Conclusions Our data suggest that nonintensive topical treatment with 0.1% gentamicin ointment for 6 weeks does not improve wound healing.